Domestic and Trade Equivalences of State Trading Importers. Issue 5 (22nd October 2013) - McCorriston, Steve; MacLaren, Donald
Abstract: Market intermediaries in importing countries in the form of state trading enterprises (STEs) involve government manipulation of market structure that can be designated a nontariff measure because they are perceived to affect market access. However, the trade effect may be only an unintended consequence of the pursuit of the domestic concerns towards which the objectives of the STE are targeted as well as the extent of the exclusive rights that it is given. These objectives may reflect concerns about domestic distortions or, where these do not exist, redistribution towards producers or consumers. To this end, identifying the domestic effects of STEs through the use of producer and consumer subsidy equivalents that complement measures of the trade distorting effect is important in gauging the overall impact of STEs. In this paper, we outline a method to measure these policy equivalences which can be readily applied to aid transparency in trade negotiations.